A study on financial management practices of small and medium enterprises in batticaloa district - Keerthigha, T.; Kengatharan, L. (University of Jaffna, 2019)
The Small and Medium sized Enterprises (SMEs) have been identified as an important sector in the overall policy objectives of the Government of Sri Lanka (GOSL) and it is seen as a driver of change for inclusive economic growth, regional development, employment generation and poverty reduction. The study aims to identify the applications of financial management practices among small and medium sized enterprises in Batticaloa district and also examine the impact of financial management practices on the performance of SMEs. Financial reporting and analysis, working capital management and financial planning and controlling have been used as variables to measure the financial management practices. Perceptions of owners on the performance were used to measure the SMEs performance. Self administered questionnaires were issued to collect data from 100 SMEs functioning in Batticaloa district. The sample was selected through stratified random sampling method from the registered SMEs in Batticaloa District. Cronbach’s Alpha was used to check the reliability of the data. Results of the study revealed that, there is a significant differences in the application of financial management practices among small and medium sized enterprises. Financial management practices in terms of financial reporting and analysis and working capital management are highly applied by medium sized enterprises than small sized enterprises. Financial reporting and analysis and working capital management have significant impact on SMEs performance. Owners of SMEs may be benefited from the study as they will able to enhance their business performance by the efficient employment of financial management practices.
Keywords: Financial management practices; Performance; SMEs